Vulnerable Worker di Provinsi Jawa Timur - Rahman, Ahmad Aulia; Sitorus, Jeffry Raja Hamonangan (Seminar Nasional Official Statistics, 2024)
Vulnerable employment has negative impacts on individuals (vulnerable workers) and regions. In 2022, there was an increase in the vulnerable employment rate in Indonesia. By province, East Java is the province with the largest number of vulnerable workers in 2022. This could lead to an increase in poverty and economic stability in East Java and other provinces in Indonesia. This study aims to determine the picture of vulnerable workers in East Java and the variables that influence their trends. The variables used in this study consist of variables derived from individual and regional characteristics sourced from Sakernas August 2022 and the East Java Gross Regional Domestic Product publication. The statistical method used is binary logistic multilevel regression to analyze the effect of variables at the individual level and regional level on the status of vulnerable workers. The results of this study show that the variables of gender, age, education level, marital status, disability status, skills training, formal work experience, manufacturing sector contribution, and agricultural sector contribution affect the tendency of the labor force to become vulnerable workers.